Navigating Remote Work and Digital Disruption through Psychological Resilience and Adaptability - Nazmah; Yani, Achmad; Setiono, Agus (Journal of Humanities and Social Sciences (JHASS), 2025)
This study investigates the direct influence of psychological resilience on individual adaptability among remote workers in Indonesian digital startups during the era of digital disruption. Amid rapid technological change and evolving work structures, psychological resilience is increasingly seen as a core competency for navigating uncertainty and maintaining adaptive performance. Using a quantitative approach, data were collected from 150 remote employees through validated instruments: the CD-RISC-10 for resilience and Pulakos Adaptive Performance scale for adaptability. Statistical analysis using SPSS 25 revealed a strong positive correlation (R = 0.945) and a high explanatory power (R² = 0.893), indicating that 89.3% of individual adaptability can be explained by psychological resilience. The regression model was statistically significant (F = 1238.748, p < 0.001), with a regression coefficient (β) of 1.635, suggesting that each unit increase in resilience results in a 1.635-point rise in adaptability. These findings affirm the essential role of resilience as a predictor of adaptive capacity in remote digital work settings. The study contributes to the limited Indonesian literature by integrating psychological constructs within the context of remote work, offering strategic insights for human resource management in facing the ongoing digital transformation.